An alkaline all-iron flow battery negative electrolyte system, a flow battery and application

CN122930969APending Publication Date: 2026-10-16JILIN UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611406216.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]但是,已开发的碱性全铁液流电池体系中,常用的有机配体如三乙醇胺等存在铁配合物的五配位不稳定结构的问题,导致其在还原过程中仍会出现一定程度的铁单质析出的副反应,进而影响电池的循环性能

Benefits of technology

[0021]本发明所述碱性全铁液流电池负极电解液体系,在负极电解液中加入储氢合金等固体增容材料,同时利用有机配体与共配体共同对铁系负极电解液进行优化,不仅使负极电解液中铁离子的配位环境更加稳定,同时可以抑制循环过程中的铁单质生成的副反应的出现,能够有效提高了全铁液流电池的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930969A_ABST
    Figure CN122930969A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of liquid flow battery, and particularly relates to a kind of alkaline full-iron liquid flow battery negative electrolyte system, liquid flow battery and application.The alkaline full-iron liquid flow battery negative electrolyte system adds solid capacity-increasing materials such as hydrogen storage alloy in negative electrolyte, and simultaneously uses organic ligand and co-ligand to optimize iron-based negative electrolyte.The alkaline full-iron liquid flow battery based on the advantages of the negative electrolyte system forms an alkaline full-iron liquid flow battery system based on redox targeting reaction, and the alkaline full-iron liquid flow battery has lower corrosion, is safe and reliable, has high energy density, lower cost and great development potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flow battery technology, specifically relating to an alkaline all-iron flow battery negative electrode electrolyte system, flow battery, and its applications. Background Technology

[0002] In recent years, with social development and people's ever-increasing energy demand, clean and renewable energy sources such as solar and wind power have been vigorously developed. However, the intermittent and discontinuous nature of these renewable energy power generation means that the generated electricity cannot be directly integrated into the power grid, severely limiting its further development. Therefore, the development of large-scale energy storage technology is urgently needed.

[0003] Flow batteries, as an emerging energy storage technology, possess advantages such as safety, reliability, low cost, and power-energy decoupling, making them a promising candidate for large-scale energy storage. Flow batteries store and release energy through active materials in a solution; therefore, their capacity and energy density are limited by the solubility of these active materials. Currently, commercially available vanadium redox flow batteries, while boasting long cycle life and high safety, suffer from high cost, and the limited solubility of vanadium ions further impacts their energy density. Therefore, there is a need in this field to develop novel flow battery systems with lower costs and higher energy density.

[0004] Currently, novel alkaline all-iron flow batteries have been developed in this field, attempting to replace more expensive vanadium-based compounds with lower-cost iron-based compounds, showing great development potential. In the developed alkaline all-iron flow battery systems, ferricyanide / ferrocyanide is used at the positive electrode, and organic ligands such as triethanolamine are used in combination with iron salts at the negative electrode to construct a fully soluble alkaline all-iron flow battery. This suppresses hydrogen evolution side reactions and eliminates defects such as dendrites during cycling.

[0005] However, in the developed alkaline all-iron flow battery systems, commonly used organic ligands such as triethanolamine suffer from the problem of unstable five-coordinate structures in iron complexes. This leads to a certain degree of iron precipitation during the reduction process, thus affecting the battery's cycle performance. Simultaneously, some iron complexes have low solubility, and the addition of large amounts of organic ligands increases solution viscosity, affecting ion transport and battery performance, thereby limiting the concentration of iron salts and ligands. Consequently, the energy density of alkaline all-iron flow batteries is relatively low. Therefore, the art seeks to develop novel alkaline all-iron flow batteries with superior performance, which would be of positive significance to the development of flow batteries. Summary of the Invention

[0006] The first objective of this invention is to provide an alkaline all-iron flow battery negative electrode electrolyte system. The negative electrode electrolyte system improves performance by optimizing the negative electrode electrolyte and adding solid compatibilizing materials, which not only makes the coordination environment of iron ions in the electrolyte more stable, but also suppresses the occurrence of side reactions of iron element generation during cycling, thus helping to improve the cycle life of the all-iron flow battery. The second objective of this invention is to provide a redox-targeted alkaline all-iron flow battery, which has the advantages of high energy density, safety, reliability, and lower cost. The third objective of this invention is to provide an alkaline all-iron flow battery negative electrode electrolyte system and its application in flow batteries.

[0007] To address the aforementioned technical problems, this invention provides an alkaline all-iron flow battery negative electrode electrolyte system, comprising a negative electrode electrolyte and a solid capacity-enhancing material; The negative electrode electrolyte comprises iron salt, organic ligand, co-ligand, alkaline electrolyte, and water; The solid compatibilizing material includes hydrogen storage alloy materials.

[0008] Specifically, in the alkaline all-iron flow battery negative electrode electrolyte system, the negative electrode electrolyte contains: The organic ligand includes at least one of triethanolamine, ethylenediaminetetraacetic acid, or 1,3-propanediaminetetraacetic acid. And / or, the concentration of the organic ligand is 0.01-5 mol / L based on the negative electrode electrolyte; And / or, the molar ratio of the organic ligand to the iron ions in the negative electrode electrolyte is 1-5:1, preferably 1.5:1.

[0009] Specifically, the alkaline all-iron flow battery negative electrode electrolyte system is characterized in that the negative electrode electrolyte contains: The coligands include at least one of nitrogen-containing monodentate or bidentate ligands such as ethylenediamine, bipyridine, glycine, propylenediamine, acetonitrile, dimethylimidazole, or imidazole. And / or, the concentration of the coligand is 0.01-5 mol / L based on the negative electrode electrolyte; And / or, the molar ratio of the coligand to the iron ions in the negative electrode electrolyte is 1-5:1, preferably 1:1.

[0010] Specifically, in the alkaline all-iron flow battery negative electrode electrolyte system, the negative electrode electrolyte contains: The iron salt includes at least one of ferric chloride, ferric sulfate, or ferric nitrate. And / or, the iron salt, calculated as iron ions, has a concentration of 0.01-5 mol / L based on the concentration of the negative electrode electrolyte, preferably 0.1-1.0 mol / L, and more preferably 0.2 mol / L.

[0011] Specifically, in the alkaline all-iron flow battery negative electrode electrolyte system, the negative electrode electrolyte contains: The alkaline electrolyte includes at least one of potassium hydroxide, sodium hydroxide, or lithium hydroxide; And / or, the alkaline electrolyte is based on the concentration of the negative electrode electrolyte at 0.01-5 mol / L, preferably 2-4 mol / L, and more preferably 3 mol / L.

[0012] Specifically, the alkaline all-iron flow battery negative electrode electrolyte system: The solid compatibilizing material includes at least one of LaNi5 type, FeTi type or TiCr2 type hydrogen storage alloy; And / or, the solid compatibilizer material may be in the form of at least one of flakes, granules or powder; And / or, the solid compatibilizing material has a mass concentration of 50-200 g / L based on the negative electrode electrolyte.

[0013] Specifically, in the alkaline all-iron flow battery negative electrode electrolyte system, the equilibrium potential difference between the hydrogen storage alloy and the iron salt in the negative electrode electrolyte is within ±200mV.

[0014] In the alkaline all-iron flow battery negative electrode electrolyte system of the present invention, the hydrogen storage alloy is one of LaNi5 type, FeTi type, and TiCr2 type. As a targeted redox solid material, it has a similar equilibrium potential to the iron complex of the all-iron flow battery negative electrode in the alkaline system. The equilibrium potential difference between the two is within ±50 mV, and a reversible targeted redox reaction can occur.

[0015] The present invention also discloses a method for preparing the negative electrode electrolyte system of the alkaline all-iron flow battery as described above, including the step of mixing the iron salt, organic ligand, co-ligand, alkaline electrolyte and water in a selected ratio to form an electrolyte, and the step of adding a solid compatibilizing material in a selected ratio to the electrolyte and completely immersing it.

[0016] This invention also discloses an alkaline all-iron flow battery, wherein the flow battery includes the negative electrode electrolyte system of the alkaline all-iron flow battery. The alkaline all-iron flow battery stores energy based on redox targeted reactions.

[0017] Specifically, the flow battery includes a positive electrode reservoir, a negative electrode reservoir, a positive electrode, a negative electrode, and a separator; The negative electrode storage tank contains the alkaline all-iron flow battery negative electrode electrolyte system, and the positive electrode storage tank contains the positive electrode electrolyte.

[0018] Specifically, in the alkaline all-iron flow battery: The positive electrode electrolyte of the flow battery includes an iron-based complex, a supporting electrolyte, and water; And / or, the positive electrode of the flow battery includes at least one of carbon felt, graphite felt, and carbon paper; And / or, the negative electrode of the flow battery includes at least one of carbon felt, graphite felt, and carbon paper; And / or, the separator of the flow battery includes an ion exchange membrane, preferably a cation exchange membrane, such as various types of cation exchange membranes such as Nafion, PTFE, and SPEEK.

[0019] Specifically, in the positive electrode electrolyte of the alkaline all-iron flow battery: The iron-based complex includes at least one of iron-based cyanide or ferrous cyanide; And / or, the iron-based complex has a concentration of 0.01-2 mol / L based on the positive electrode electrolyte; And / or, the supporting electrolyte includes at least one of potassium hydroxide, sodium hydroxide, or lithium hydroxide; And / or, the supporting electrolyte has a concentration of 0.05-5 mol / L based on the positive electrode electrolyte.

[0020] The present invention also discloses the alkaline all-iron flow battery negative electrode electrolyte system or the application of the alkaline all-iron flow battery in the field of energy storage technology.

[0021] The alkaline all-iron flow battery negative electrode electrolyte system of this invention incorporates solid capacity-enhancing materials such as hydrogen storage alloys into the negative electrode electrolyte. Simultaneously, organic ligands and co-ligands are used to optimize the iron-based negative electrode electrolyte. This not only makes the coordination environment of iron ions in the negative electrode electrolyte more stable but also suppresses the occurrence of side reactions leading to the formation of elemental iron during cycling, effectively improving the cycle life of the all-iron flow battery.

[0022] In the alkaline all-iron flow battery negative electrode electrolyte system of the present invention, a solid capacity-enhancing material is introduced into the negative electrode electrolyte. By means of redox targeted reaction, the capacity and energy density of the battery are effectively improved, thus effectively ensuring the application performance and efficiency of the flow battery.

[0023] The alkaline all-iron flow battery of the present invention, based on the advantages of the negative electrode electrolyte system, forms an alkaline all-iron flow battery system based on redox targeted reaction. Compared with the traditional all-vanadium flow battery, the targeted all-iron flow battery of the present invention has lower corrosion, is safe and reliable, has high energy density, and lower cost, and has great development potential.

[0024] The alkaline all-iron flow battery of this invention optimizes the negative electrode electrolyte system by introducing inexpensive, safe and environmentally friendly coligands, thereby achieving stable coordination of iron ions under alkaline conditions to reduce side reactions. Furthermore, the addition of solid capacity-enhancing materials introduces reversible redox targeted reactions and enables energy storage through solid materials, thus achieving a dual improvement in the cycle stability and energy density of the all-iron flow battery. It has great development prospects in the field of large-scale energy storage. Attached Figure Description

[0025] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein: Figure 1 This is a schematic diagram illustrating the working process of the redox-targeted alkaline all-iron flow battery of the present invention. Figure 2 A comparison graph of charge-discharge curves of the assembled batteries in Example 1 and Comparative Example 1; Figure 3 The diagram shows the charging capacity, discharging capacity, and coulombic efficiency of the battery assembled in Example 8. In the battery shown, 3.6g of solid capacity-enhancing material was added after the battery was cycled 5 times. Figure 4 The graph shows a comparison of the discharge capacity and cycle time of the assembled batteries in Examples 1, 3, and 5 with those in Comparative Examples 1, 3, 5, 8, and 11. Figure 5 The graph shows a comparison of the coulombic efficiency, initial discharge capacity, and discharge capacity after 250 hours for the batteries assembled in Examples 1, 3, and 5 and Comparative Examples 1, 3, 5, 8, and 11. Detailed Implementation

[0026] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.

[0027] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art may make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0029] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0030] In the following embodiments of the present invention, in order to improve the application performance such as energy density of alkaline all-iron flow batteries, an alkaline all-iron flow battery negative electrode electrolyte system is improved, which includes a negative electrode electrolyte and a solid capacity-enhancing material; The negative electrode electrolyte comprises iron salt, organic ligand, co-ligand, alkaline electrolyte and water; The solid compatibilizing material includes hydrogen storage alloy materials.

[0031] In some specific embodiments, the solid compatibilizing material is placed in the negative electrode storage tank and completely immersed in the negative electrode electrolyte. A filter structure is provided to fix the hydrogen storage alloy in the storage tank, ensuring that the two are in full contact.

[0032] In some specific embodiments, the organic ligand in the negative electrode electrolyte includes at least one of triethanolamine, ethylenediaminetetraacetic acid, or 1,3-propanediaminetetraacetic acid.

[0033] In some specific embodiments, the concentration of the organic ligand in the negative electrode electrolyte is 0.01-5 mol / L based on the concentration of the negative electrode electrolyte.

[0034] In some specific embodiments, the molar ratio of the organic ligand to the iron ions in the negative electrode electrolyte is 1-5:1, preferably 1.5:1.

[0035] In some specific embodiments, the co-ligand in the negative electrode electrolyte includes at least one of nitrogen-containing monodentate or bidentate ligands such as ethylenediamine, bipyridine, glycine, propylenediamine, acetonitrile, dimethylimidazole, or imidazole.

[0036] In some specific embodiments, the concentration of the coligand in the negative electrode electrolyte is 0.01-5 mol / L based on the concentration of the negative electrode electrolyte.

[0037] In some specific embodiments, the molar ratio of the coligand to the iron ions in the negative electrode electrolyte is 1-5:1, preferably 1:1.

[0038] In some specific embodiments, the iron salt in the negative electrode electrolyte includes at least one of ferric chloride, ferric sulfate, or ferric nitrate.

[0039] In some specific embodiments, the concentration of the iron salt in the negative electrode electrolyte, based on the iron ion content of the negative electrode electrolyte, is 0.01-5 mol / L, preferably 0.1-1.0 mol / L, and more preferably 0.2 mol / L.

[0040] In some specific embodiments, the alkaline electrolyte in the negative electrode electrolyte includes at least one of potassium hydroxide, sodium hydroxide, or lithium hydroxide.

[0041] In some specific embodiments, the alkaline electrolyte in the negative electrode electrolyte has a concentration of 0.01-5 mol / L, preferably 2-4 mol / L, and more preferably 3 mol / L.

[0042] In some specific embodiments, the solid compatibilizing material in the negative electrode electrolyte includes at least one of LaNi5 type, FeTi type, or TiCr2 type hydrogen storage alloys.

[0043] In some specific embodiments, the solid compatibilizing material in the negative electrode electrolyte has a mass concentration of 50-200 g / L based on the negative electrode electrolyte; As an exemplary embodiment, in the following embodiment of the present invention, the flow battery includes a negative electrode reservoir, a positive electrode reservoir, a negative electrode, a positive electrode, and a separator. The negative electrode reservoir contains the negative electrode electrolyte system (i.e., negative electrode electrolyte and solid compatibilizer material), and the positive electrode reservoir contains the positive electrode electrolyte.

[0044] In some specific embodiments, the positive electrode electrolyte of the flow battery includes an iron-based complex, a supporting electrolyte, and water.

[0045] In some specific embodiments, the iron-based complex in the positive electrode electrolyte includes at least one of iron-based cyanide or ferrous cyanide.

[0046] In some specific embodiments, the concentration of the iron-based complex in the positive electrode electrolyte is 0.01-2 mol / L based on the concentration of the positive electrode electrolyte.

[0047] In some specific embodiments, the supporting electrolyte in the positive electrode electrolyte includes at least one of potassium hydroxide, sodium hydroxide, or lithium hydroxide.

[0048] In some specific embodiments, the concentration of the supporting electrolyte in the positive electrode electrolyte is 0.05-5 mol / L.

[0049] In some specific embodiments, the positive electrode of the flow battery includes at least one of carbon felt, graphite felt, and carbon paper.

[0050] In some specific embodiments, the negative electrode of the flow battery includes at least one of carbon felt, graphite felt, and carbon paper.

[0051] In some specific embodiments, the separator of the flow battery includes an ion exchange membrane, preferably a cation exchange membrane, such as various types of cation exchange membranes such as Nafion, PTFE, and SPEEK.

[0052] Figure 1 This is a schematic diagram illustrating the working process of an exemplary redox-targeted alkaline all-iron flow battery during a charge-discharge cycle. Its exemplary positive electrode active material is Fe(CN)6. 3- / Fe(CN)6 4- In the negative electrode electrolyte, the addition of organic ligands such as triethanolamine (TEA) and co-ligands such as ethylenediamine (EDA) forms an iron complex (FeTEAEDA) with iron salts, serving as the negative electrode active material. The solid compatibilizer material for the negative electrode is a hydrogen storage alloy (MH). - Represents electron transfer, ΔE cell The figure shows the potential difference between the positive and negative electrodes, and the reaction between the iron active material at the negative electrode and the solid compatibilizer.

[0053] Taking the charging process as an example, during charging, the active material in the negative electrode electrolyte undergoes an electrochemical reaction at the electrode. The reaction equation is as follows: ; After the negative electrode active material has reacted at the electrode, it flows back into the negative electrode storage tank, where it undergoes a chemical reaction with the solid compatibilizer material. The reaction equation is as follows: ; This reaction reduces the oxidized solid compatibilizer to a reduced state, while the active material is oxidized to an oxidized state. As the electrolyte circulates, the reaction can be repeated at the electrode.

[0054] The above process is repeated during charging until all oxidized solid compatibilizer materials are reduced to their reduced state. During this process, energy is jointly stored by the negative electrode active material and the solid compatibilizer materials. The reaction principle during discharging is the same as during charging, with the negative electrode active material and the solid compatibilizer materials synergistically releasing energy. In battery cycling, the solid capacity contributes to the overall flow battery, resulting in increased battery capacity and energy density.

[0055] In the following embodiments of the present invention, a flow battery of the corresponding system is assembled according to conventional methods in the art.

[0056] Example 1 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. Then, 0.01 mol of the co-ligand ethylenediamine was added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0057] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), ethylenediamine (0.2 mol / L), and potassium hydroxide (3 mol).

[0058] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0059] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0060] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0061] Example 2 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand bipyridine was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0062] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), bipyridine (0.2 mol / L), and potassium hydroxide (3 mol).

[0063] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0064] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0065] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0066] Example 3 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand glycine was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0067] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), glycine (0.2 mol / L), and potassium hydroxide (3 mol).

[0068] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0069] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0070] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0071] Example 4 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. Then, 0.01 mol of the co-ligand propylenediamine was added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0072] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), propylenediamine (0.2 mol / L), and potassium hydroxide (3 mol).

[0073] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0074] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0075] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0076] Example 5 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand acetonitrile was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0077] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), acetonitrile (0.2 mol / L), and potassium hydroxide (3 mol).

[0078] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0079] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0080] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0081] Example 6 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand dimethylimidazole was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0082] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), dimethylimidazole (0.2 mol / L), and potassium hydroxide (3 mol).

[0083] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0084] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0085] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0086] Example 7 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand imidazole was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0087] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), imidazole (0.2 mol / L), and potassium hydroxide (3 mol).

[0088] 3.6 g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0089] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0090] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0091] Example 8 Negative Electrolyte System 0.01 mol of FeCl3 was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand triethanolamine was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. Then, 0.01 mol of the co-ligand ethylenediamine was added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0092] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of a negative electrode electrolyte containing 0.2 mol / L iron ions, 0.3 mol / L triethanolamine, 0.2 mol / L ethylenediamine, and 3 mol potassium hydroxide. Before use, purge the prepared negative electrode electrolyte with nitrogen for 30 min to remove dissolved oxygen.

[0093] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0094] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0095] After the flow battery has run for five cycles, 3.6g of LaNi5 hydrogen storage alloy is added to the negative electrode electrolyte as a solid capacity enhancer. During the addition, a nitrogen atmosphere is maintained, and the hydrogen storage alloy is completely immersed in the negative electrode electrolyte.

[0096] Example 9 Negative Electrolyte System 0.01 mol of ferric nitrate was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand ethylenediaminetetraacetic acid was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand ethylenediamine was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0097] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L) - ethylenediaminetetraacetic acid (0.3 mol / L) - ethylenediamine (0.2 mol / L) - potassium hydroxide (3 mol).

[0098] 3.6 g of FeTi-type hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0099] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0100] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0101] Example 10 Negative Electrolyte System 0.01 mol of ferric nitrate was added to 25 mL of deionized water and stirred until completely dissolved to obtain the first solution. 0.015 mol of the organic ligand 1,3-propanediaminetetraacetic acid was added dropwise to the first solution, and the mixture was stirred for 30 min until a homogeneous second solution was formed. 0.01 mol of the co-ligand ethylenediamine was then added to the second solution, and the mixture was stirred thoroughly for 30 min to obtain the precursor solution.

[0102] Add 0.15 mol of potassium hydroxide to the precursor solution and stir for 1 h until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of negative electrode electrolyte containing iron ions (0.2 mol / L)-1,3-propanediaminetetraacetic acid (0.3 mol / L)-ethylenediamine (0.2 mol / L)-potassium hydroxide (3 mol).

[0103] 3.6 g of TiCr2-type hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte. Before use, the prepared negative electrode electrolyte was purged with nitrogen for 30 min to remove dissolved oxygen.

[0104] Positive Electrolyte Add 0.02 mol K₄Fe(CN)₆ to 30 mL of deionized water and stir for 10 min until the precipitate is completely dissolved to obtain the first solution. Add 0.125 mol NaOH to the first solution and stir for 30 min until the solution is clear and transparent. Transfer the solution to a 50 mL volumetric flask and dilute to 50 mL with deionized water to obtain 50 mL of positive electrode electrolyte containing 0.4 M K₄Fe(CN)₆ and 4 M NaOH, for later use.

[0105] All-ferrofluid battery assembly In this embodiment, a single flow battery is assembled in the following order: positive electrode components (positive electrode plate, copper current collector, positive graphite electrode plate, graphite carbon felt), Speek separator, and negative electrode components (graphite carbon felt, negative graphite electrode plate, copper current collector, negative electrode plate). The graphite carbon felt has a size of 2cm × 2.5cm × 6mm. The positive electrode reservoir, negative electrode reservoir, and battery body are connected to each other by a peristaltic pump.

[0106] Example 11 Negative Electrolyte System Referring to the negative electrode electrolyte system in Example 1, prepare 50 mL of a negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), ethylenediamine (0.2 mol / L), and potassium hydroxide (3 mol).

[0107] 2.5g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte.

[0108] Positive Electrolyte Referring to the positive electrode electrolyte in Example 1, prepare 50 mL of a positive electrode electrolyte containing 0.4 M K4Fe(CN)6 and 4 M NaOH.

[0109] All-ferrofluid battery assembly The flow battery was assembled according to the structure and method described in Example 1.

[0110] Example 12 Negative Electrolyte System Referring to the negative electrode electrolyte system in Example 1, prepare 50 mL of a negative electrode electrolyte containing iron ions (0.2 mol / L), triethanolamine (0.3 mol / L), ethylenediamine (0.2 mol / L), and potassium hydroxide (3 mol).

[0111] 10g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte.

[0112] Positive Electrolyte Referring to the positive electrode electrolyte in Example 1, prepare 50 mL of a positive electrode electrolyte containing 1 M K4Fe(CN)6 and 4 M NaOH.

[0113] All-ferrofluid battery assembly The flow battery was assembled according to the structure and method described in Example 1.

[0114] Example 13 Negative Electrolyte System Referring to the negative electrode electrolyte system in Example 1, prepare 50 mL of a negative electrode electrolyte containing iron ions (0.01 mol / L), triethanolamine (0.01 mol / L), ethylenediamine (0.01 mol / L), and potassium hydroxide (0.01 mol).

[0115] 3.6g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte.

[0116] Positive Electrolyte Referring to the positive electrode electrolyte in Example 1, prepare 50 mL of a positive electrode electrolyte containing 0.01 M K4Fe(CN)6 and 0.05 M NaOH.

[0117] All-ferrofluid battery assembly The flow battery was assembled according to the structure and method described in Example 1.

[0118] Example 14 Negative Electrolyte System Referring to the negative electrode electrolyte system in Example 1, prepare 50 mL of negative electrode electrolyte containing iron ions (5 mol / L), triethanolamine (5 mol / L), ethylenediamine (5 mol / L), and potassium hydroxide (5 mol).

[0119] 3.6g of LaNi5 hydrogen storage alloy was added to the negative electrode electrolyte as a solid compatibilizer, and the hydrogen storage alloy was completely immersed in the negative electrode electrolyte.

[0120] Positive Electrolyte Referring to the positive electrode electrolyte in Example 1, prepare 50 mL of a positive electrode electrolyte containing 2 M K4Fe(CN)6 and 5 M NaOH.

[0121] All-ferrofluid battery assembly The flow battery was assembled according to the structure and method described in Example 1.

[0122] Comparative Example 1 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 1, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0123] Comparative Example 2 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 2, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0124] Comparative Example 3 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 3, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0125] Comparative Example 4 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 4, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0126] Comparative Example 5 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 5, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0127] Comparative Example 6 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 6, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0128] Comparative Example 7 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 7, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system.

[0129] Comparative Example 8 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 1, except that the hydrogen storage alloy is not added to the negative electrode electrolyte system, and the coligand is not added to the negative electrode electrolyte.

[0130] Comparative Example 9 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 1. The only difference is that the hydrogen storage alloy is not added to the negative electrode electrolyte system, the coligand ethylenediamine is not added to the negative electrode electrolyte, and triethanolamine is replaced with an equimolar amount of ethylenediaminetetraacetic acid.

[0131] Comparative Example 10 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Example 1. The only difference is that the hydrogen storage alloy is not added to the negative electrode electrolyte system, the coligand ethylenediamine is not added to the negative electrode electrolyte, and triethanolamine is replaced with an equimolar amount of 1,3-propanediaminetetraacetic acid.

[0132] Comparative Example 11 The structure, material system, and assembly method of the flow battery described in this comparative example are the same as those in Comparative Example 1, except that the coligand is not added to the negative electrode electrolyte system.

[0133] Experimental Example In this experimental example, the performance of the flow batteries assembled in Examples 1-12 and Comparative Examples 1-11 above was tested.

[0134] Test conditions for all-ferrous flow batteries: The flow rate of the peristaltic pump was controlled at 60 mL / min; the battery testing instrument used was the Blue Electric testing system; constant current testing was employed; and the current density was 80 mA / cm². 2 The test voltage range is (0.7V-1.7V).

[0135] The test results in this experiment are shown in Table 1 below.

[0136] In this experimental example, the charge-discharge curves of the assembled batteries in Example 1 and Comparative Example 1 are shown in the attached figure. Figure 2As shown in the attached figure, the charging capacity, discharging capacity, and coulombic efficiency of the battery assembled in Example 8 are illustrated. Figure 3 As shown in the attached figure, the discharge capacity and cycle time of the assembled batteries in Examples 1, 3, and 5 are compared with those in Comparative Examples 1, 3, 5, 8, and 11. Figure 4 As shown in the attached figure, the coulombic efficiency, initial discharge capacity, and discharge capacity after 250 hours of the batteries assembled in Examples 1, 3, and 5 are compared with those in Comparative Examples 1, 3, 5, 8, and 11. Figure 5 As shown.

[0137] Table 1 Performance of All-Iron Flow Batteries

[0138] Combined with Table 1 and appendix Figure 2 The results show that, under the same electrolyte configuration and battery testing conditions, the all-iron targeted battery of Example 1 with added hydrogen storage alloy exhibits a charging capacity increase of approximately 293 mAh and a discharging capacity increase of approximately 282 mAh compared to the battery of Comparative Example 1 without added hydrogen storage alloy. Furthermore, the volume of 3.6 g of hydrogen storage alloy, calculated by the water displacement method, is approximately 0.7 mL, representing only about 1.38% of the negative electrode electrolyte volume. This slight increase in volume results in more than a doubling of capacity and energy density, demonstrating a significant technological advantage.

[0139] Combined with Table 1 and appendix Figure 3 As shown in the results, when the flow battery described in Example 8 is operated with the addition of a hydrogen storage alloy, its charge and discharge capacity is immediately and significantly improved, while the coulombic efficiency of the battery remains almost unchanged. The battery can achieve stable long-term operation after the addition of the alloy, which intuitively demonstrates the advantages of the hydrogen storage material.

[0140] Combined with Table 1 and appendix Figure 4The results show that, under the same battery testing conditions, the battery assembled in Comparative Example 8 without the co-ligand exhibited poor cycle stability and high capacity decay due to the unstable coordination structure of the iron complex. In contrast, the flow batteries assembled in Examples 1, 3, and 5 with the co-ligand showed significantly improved cycle stability compared to Comparative Example 8, maintaining stable operation without capacity decay for a period of time. The scheme with ethylenediamine as the co-ligand showed the most significant improvement, with the corresponding battery cycling for 300 hours without capacity decay. Batteries assembled with glycine, propylenediamine, dimethylimidazole, and imidazole respectively performed well, maintaining capacity without decay for 230 hours. Batteries assembled with bipyridine and acetonitrile showed slightly less improvement, maintaining capacity without decay for 160 hours. This demonstrates that the addition of co-ligands plays a significant role in improving the stability of the coordination structure of the iron complex in the negative electrode electrolyte system. Examples 1, 3, and 5, which incorporate hydrogen storage alloys, show significant improvements in battery capacity and cycle life compared to their corresponding comparative examples 1, 3, 5, and 8. Even Comparative example 11, which only incorporates hydrogen storage alloys without co-ligands, exhibits some performance improvement. This demonstrates that the addition of solid compatibilizer hydrogen storage alloys to the negative electrode electrolyte system enables targeted reactions between the alloys and iron complexes, thereby significantly increasing battery capacity and energy density.

[0141] Combined with Table 1 and appendix Figure 5 The results show that the all-iron flow battery assembled by adding coligands and solid capacity-enhancing materials in this invention has higher performance than the flow battery assembled without adding coligands or solid capacity-enhancing materials. In particular, the battery assembled in Example 1, which adds ethylenediamine as a coligand and hydrogen storage alloy as a solid capacity-enhancing material, has a coulombic efficiency that is 11.32% higher than that of Comparative Example 8, which does not add coligands and solid capacity-enhancing materials, an initial discharge capacity that is 330 mAh higher, and a discharge life that is significantly improved.

[0142] In summary, the alkaline all-iron flow battery negative electrode electrolyte system of this invention incorporates solid capacity-enhancing materials such as hydrogen storage alloys into the negative electrode electrolyte. Simultaneously, the optimization of the iron-based negative electrode electrolyte using organic ligands and co-ligands not only makes the coordination environment of iron ions in the negative electrode electrolyte more stable but also suppresses the occurrence of side reactions leading to the formation of elemental iron during cycling, effectively improving the cycle life of the all-iron flow battery.

[0143] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. An alkaline all-iron flow battery negative electrode electrolyte system, characterized in that, Including negative electrode electrolyte and solid compatibilizer materials; The negative electrode electrolyte comprises iron salt, organic ligand, co-ligand, alkaline electrolyte, and water; The solid compatibilizing material includes hydrogen storage alloy materials.

2. The alkaline all-iron flow battery negative electrode electrolyte system according to claim 1, characterized in that, In the negative electrode electrolyte: The organic ligand includes at least one of triethanolamine, ethylenediaminetetraacetic acid, or 1,3-propanediaminetetraacetic acid. And / or, the concentration of the organic ligand is 0.01-5 mol / L based on the negative electrode electrolyte; And / or, the molar ratio of the organic ligand to the iron ions in the negative electrode electrolyte is 1-5:

1.

3. The alkaline all-iron flow battery negative electrode electrolyte system according to claim 1, characterized in that, In the negative electrode electrolyte: The coligand includes at least one of ethylenediamine, bipyridine, glycine, propylenediamine, acetonitrile, dimethylimidazole, or imidazole; And / or, the concentration of the coligand is 0.01-5 mol / L based on the negative electrode electrolyte; And / or, the molar ratio of the coligand to the iron ions in the negative electrode electrolyte is 1-5:

1.

4. The alkaline all-iron flow battery negative electrode electrolyte system according to claim 1, characterized in that, In the negative electrode electrolyte: The iron salt includes at least one of ferric chloride, ferric sulfate, or ferric nitrate. And / or, the iron salt, calculated as iron ions, has a concentration of 0.01-5 mol / L based on the concentration of the negative electrode electrolyte.

5. The alkaline all-iron flow battery negative electrode electrolyte system according to claim 1, characterized in that, In the negative electrode electrolyte: The alkaline electrolyte includes at least one of potassium hydroxide, sodium hydroxide, or lithium hydroxide; And / or, the alkaline electrolyte has a concentration of 0.01-5 mol / L based on the concentration of the negative electrode electrolyte.

6. The alkaline all-iron flow battery negative electrode electrolyte system according to any one of claims 1-5, characterized in that: The solid compatibilizing material includes at least one of LaNi5 type, FeTi type or TiCr2 type hydrogen storage alloy; And / or, the solid compatibilizer material may be in the form of at least one of flakes, granules or powder; And / or, the solid compatibilizing material has a mass concentration of 50-200 g / L based on the negative electrode electrolyte.

7. An alkaline all-iron flow battery, characterized in that, The flow battery includes the alkaline all-iron flow battery negative electrode electrolyte system according to any one of claims 1-6.

8. The alkaline all-iron flow battery according to claim 7, characterized in that: The positive electrode electrolyte of the flow battery includes an iron-based complex, a supporting electrolyte, and water; And / or, the positive electrode of the flow battery includes at least one of carbon felt, graphite felt, and carbon paper; And / or, the negative electrode of the flow battery includes at least one of carbon felt, graphite felt, and carbon paper; And / or, the separator of the flow battery includes an ion exchange membrane.

9. The alkaline all-iron flow battery according to claim 8, characterized in that, In the positive electrode electrolyte: The iron-based complex includes at least one of iron-based cyanide or ferrous cyanide; And / or, the iron-based complex has a concentration of 0.01-2 mol / L based on the positive electrode electrolyte; And / or, the supporting electrolyte includes at least one of potassium hydroxide, sodium hydroxide, or lithium hydroxide; And / or, the supporting electrolyte has a concentration of 0.05-5 mol / L based on the positive electrode electrolyte.

10. The application of an alkaline all-iron flow battery negative electrode electrolyte system as described in any one of claims 1-6 or an alkaline all-iron flow battery as described in any one of claims 7-9 in the field of energy storage technology.